Investigation of structural resorption behavior of biphasic bioceramics with help of gravimetry, μCT, SEM, and XRD. Issue 3 (7th May 2015) - de Wild, Michael; Amacher, Fabienne; Bradbury, Christopher R.; Molenberg, Aart
Abstract: Resorbable bone substitute materials are widely used for bone augmentation after tumor resection, parallel to implant placement, or in critical size bone defects. In this study, the structural dissolution of a biphasic calcium phosphate bone substitute material with a hydroxyapatite (HA)/tricalcium phosphate (β‐TCP) ratio of 60/40 was investigated by repeatedly placing porous blocks in EDTA solution at 37 °C. At several time points, the blocks were investigated by SEM, µCT, and gravimetry. It was found that always complete 2–3 µm sized grains were removed from the structure and that the β‐TCP is dissolved more rapidly. This selective dissolution of the β‐TCP grains was confirmed by XRD measurements. The blocks were eroded from the outside toward the center. The structure remained mechanically stable because the central part showed a delayed degradation and because the slower dissolving HA grains preserved the integrity of the structure. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 546–553, 2016.